2012
DOI: 10.1063/1.4720397
|View full text |Cite|
|
Sign up to set email alerts
|

Electrostatically driven collapsible Au thin films assembled using transfer printing for thermal switching

Abstract: We report deterministic assembly of 100 nm thick suspended gold films using transfer printing that are mechanically collapsible. We demonstrate the latter using electrostatic force to establish and break physical contact between the film and a silicon dioxide substrate in a reversible and repeatable manner. Modeling the thermal conductance at the interface between the suspended film and the substrate, we show that the fabricated structure behaves as a thermal switch. The on-state corresponds to the collapsed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…It is worth noting that whereas thermal conductance foreseen in Ref. 12 comes from theoretical calculations our result stems from experiments and therefore it represents a extremely promising milestone for TSs optimization. Comparison to existing thermal switches 4,10 shows a ratio 10 times higher with a thermal conductance ratio η = 10 3 .…”
Section: Figmentioning
confidence: 86%
See 2 more Smart Citations
“…It is worth noting that whereas thermal conductance foreseen in Ref. 12 comes from theoretical calculations our result stems from experiments and therefore it represents a extremely promising milestone for TSs optimization. Comparison to existing thermal switches 4,10 shows a ratio 10 times higher with a thermal conductance ratio η = 10 3 .…”
Section: Figmentioning
confidence: 86%
“…Here, to achieve repeatable switching with thin films, we use electrostatic forces for actuation. The concept has been used and it is shown that it is possible to establish reversible and repeatable mechanical contact led by electrostatic forces with a thin gold film 12 . This method has recently demonstrated its effectiveness for an electrocaloric based cooling system 13 where a power density of 3 W g −1 and a coefficient of performance of 13 have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Being able to assemble Au films with micro-masonry hugely improves wide adaptation of the micro-masonry manufacturing scheme since it introduces a metal type of material. Due to its low electrical contact resistance with silicon, it can be used as an electrode in the finalized MEMS devices as well as a suspended membrane flexure as presented in Keum et al 9 Transferrable inks developed are currently limited to Si and Au and the materials of their corresponding receiver substrates are Si and SiO 2 for Si, and Au and Si for Au. Overall, larger contact area between a receiver substrate and an ink results in ease in the printing step.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-masonry provides several attractive features not present in other methods: (a) the ability to integrate functional and structural solid inks of dissimilar materials to assemble MEMS sensors and actuators all integrated within the 3D structure; (b) the interfaces of assembled solid inks can function as electrical and thermal contacts 9,10 ; (c) the assembly spatial resolution can be high (~1 μm) by utilizing highly-scalable and wellunderstood lithographic processes for generating solid inks and highly-precise mechanical stages for transfer printing 7 ; and (d) functional and structural solid inks can be integrated on both rigid and flexible substrates in planar or curvilinear geometries.…”
Section: Introductionmentioning
confidence: 99%